(untitled) (Global Journal of Management and Business Research, 2014)
The objective of this study was to analyze the scientific production and training in management accounting of doctors in Brazil. To achieve this objective, six Brazilian accounting journals were selected according to Qualis from CAPES (Coordenação de Aperfeiçoamento de Pessoal de Nível Superior -Brazilian Federal Agency for Support and Evaluation of Graduate Education),published from 2001 to 2013, as well as doctoral dissertations in accounting published from 1962 to 2013. The results showed an increase in publications at the beginning of the period analyzed and a slight decrease over the past two years. The training of doctors in management accounting underwent an increase in absolute terms, which in some ways was a reflection of the growth in recent years of doctoral education in accounting in Brazil.